La esperanza de Sócrates:: ¿cuestión de argumentos o encantamientos? (Notas al Fedón) - Bossi, Beatriz (Revista Archai, 2015)
Abstract: In this paper, I would like to make a comparison between non-argumentative resources (such as Socrates’ decision to write poetry, the mention of the teletai and the bakchoi as those who have philosophized correctly and the 'incantations' to soothe the soul) on the one hand, and the well-known rational arguments presented in the dialogue, on the other hand, with the aim of establishing what weight each of them has to hold Socrates’ hope. I assume that it is not possible to separate these two types of resources, though they can be clearly distinguished and subordinated. I understand that Plato deliberately provides a fine web made of both powers, because emotion and reason, myth and logos, imagination and argument, poetry and philosophy, desire and intellectual prescriptions are for him an expression of man's natural constituent elements that deserve our care in due proportion. This Socratic devotion to reduce the fear in the hearts of his friends and to awaken in them the desire of spending their lives philosophizing, turns out to be an interesting challenge to us. I will also attempt to make sense of some of the issues that provoke Socrates’ puzzles, such as the mixed nature of pleasure, the divine ‘order’ to produce poetry at the last moment (i.e. a lower kind of music, compared to philosophy) and the meaning of a hope founded on a risky belief. Keywords: poetry-philosophy, incantations-arguments, life-death, body-soul, pleasure-pain.